Recruitment of Dry Tropical Woody Species After Fire: Germination Phase and Seedling Establishment - Ibañez Moro, Amalia Valeria (2025)
The objective of this study was to evaluate the effect of fire on the recruitment of six woody species sown at two soil depths. The study area was the western Argentine Chaco region, South America. The selected species were Aspidosperma quebracho-blanco Schlecht, Schinopsis lorentzii (Griseb.) Engl., Sarcomphalus mistol (Griseb.) Hauenschild, Neltuma nigra (Griseb.) Hieron, Senegalia gilliesii (Steud.) Seigler & Ebinger, and Vachellia aroma (Gillies ex Hook. & Arn.) Seigler & Ebinger. Seedling emergence was monitored following experimental burns (EB) in 2017 and 2019 under similar environmental conditions. In 2017, seeds were placed on the litter layer in 2 × 2 m plots; in 2019, seeds were buried at 2 cm depth in 2.5 × 10 m plots. Field emergence was recorded, and viability of non-germinated seeds was tested in the lab. Recruitment was also assessed two years post-EB 2017 in 20 plots (2 × 5 m) under burnt and control conditions. No emergence occurred from seeds on the litter layer, but S. lorentzii and N. nigra germinated in the laboratory (<7%, significant difference, p < 0.0001). All species with buried seeds germinated in the field, with significant differences among species and compared to controls (p < 0.0027). Field recruitment revealed regeneration of A. quebracho-blanco, N. nigra, and S. gilliesii in the burnt area, with variations in seedling size and density.